2018
DOI: 10.3892/or.2018.6607
|View full text |Cite
|
Sign up to set email alerts
|

Genome‑scale analysis to identify potential prognostic microRNA biomarkers for predicting overall survival in patients with colon adenocarcinoma

Abstract: The aim of the present study was to identify potential prognostic microRNA (miRNA) biomarkers for colon adenocarcinoma (COAD) prognostic prediction using the dataset of The Cancer Genome Atlas (TCGA). The genome-wide miRNA sequencing dataset and corresponding COAD clinical information were downloaded from TCGA. Prognosis-related miRNA screening was performed by genome-wide multivariable Cox regression analysis and used for prognostic signature construction. Ten miRNAs (hsa-mir-891a, hsa-mir-6854, hsa-mir-216a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…At present, the diagnosis of COAD has many problems, such as poor specificity and low time efficiency (Benson et al, 2017;Sun et al, 2019). (Li et al, 2018b;Wei et al, 2018). For this reason, it is critical to find prognostic biomarkers for the treatment of COAD.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the diagnosis of COAD has many problems, such as poor specificity and low time efficiency (Benson et al, 2017;Sun et al, 2019). (Li et al, 2018b;Wei et al, 2018). For this reason, it is critical to find prognostic biomarkers for the treatment of COAD.…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that hsa-mir-486-1 may serve as a potential diagnostic biomarker of lung adenocarcinoma ( Ren et al, 2019 ). Hsa-mir-6854 was reported as a potential prognostic miRNA biomarker for colon adenocarcinoma ( Wei et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The data analyzed in this study were all obtained from public databases. The training cohort datasets were downloaded from TCGA ( https: // tcga - data.nci.nih.gov / tcga ) [ 23 ], and the validation datasets were obtained from GEO ( https://www.ncbi.nlm.nih.gov/geo/ ). The training cohort datasets included clinical datasets ( n = 452), transcriptome datasets ( n = 449), and verification datasets from GSE39582 ( n = 585) [ 24 ] and GSE17538 ( n = 244) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%